A Perspective on Cost Drivers. - Dopuch, Nicholas (The Accounting Review, 1993)
My task is to provide a perspective regarding the general topic of choosing optimal cost drivers, as that topic is reflected in the selected articles of this Forum. This perspective can be developed more easily if I first digress back to the 1960s when managerial accounting research was beginning to evolve to its present stages. In the 1960s, teaching and research in managerial accounting were heavily influenced by the growing popularity of operations research and management science approaches to business problems. These approaches were largely normative in nature, consisting basically of optimization techniques that, if implemented, promised to improve managerial decision making. Their normative character was carried over into managerial accounting as well, with the basic theme of many managerial accounting articles in that era being, "Here is how optimization techniques may be used to guide the design of improved managerial accounting systems." Rarely, if ever, did the researcher provide empirical evidence or other forms of proof that the new systems would in fact lead to improvements in managerial decisions. Rather, the main result provided was that the new systems could generate new accounting numbers under certain assumed conditions. If these new numbers appeared to be materially different from the old, implementation of the new systems could lead to changes in managers' decisions. The changes in managers' decisions were assumed to be desirable ones to induce. However, desirability was based primarily on subjective criteria adopted by the researcher. Generally, a necessary condition for potential improvements in managerial decisions from new accounting systems is that the new system generate accounting numbers that are materially different from those obtained from the existing system. For this reason, I label such studies as materiality studies, since they basically follow the traditional materiality rule in accounting. But different accounting numbers might not lead to changes in decisions that result in payoffs sufficient to justify the costs of implementing the new systems. Indeed, recognition of this basic limitation of materiality studies was a strong motivation for managerial accounting researchers to investigate the advantages of using the information economics paradigm to estimate the net payoffs from implementing new accounting systems. Recall that information economics is a conceptual framework that can be used to assess how new information will affect managerial decisions and, assuming decisions will change, the expected payoffs from implementing a new accounting information system. Included in the framework Is an assumed decision-maker with a particular utility function who processes information through a specific decision model. The model, in turn, yields an ex ante optimal decision. The value of new information is then measured as the change in the net payoffs induced by moving from a previous optimal decision to a revised optimal decision under the assumption that the new information does in fact induce a revision in the optimal decision. Note that the original optimal decision might still remain optimal even though the new information received by the decision maker differs from the old. Obviously, the conclusion in the latter case is that the new information system would have either a zero or negative expected net value.